2015
DOI: 10.4238/2015.september.8.12
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vitamin D receptor (VDR) polymorphisms and the efficacy of recombinant human growth hormone (rhGH) treatment in children with idiopathic short stature

et al.

Abstract: ABSTRACT. Polymorphisms in the vitamin D receptor (VDR) gene are associated with idiopathic short stature (ISS) in several countries. This study aimed to identify a possible correlation between polymorphisms in the VDR promoter in Chinese children with ISS and the efficacy of the recombinant human growth hormone (rhGH) treatment. Pre-pubertal children with ISS and healthy age-and gendermatched children (N = 95 each) were enrolled in this study. Two single nucleotide polymorphisms (SNPs) in the VDR promoter (rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
4
0
4
Order By: Relevance
“…25-(OH)D has long been existed in the body and good stability, so it is currently considered to be an important indicator reflecting the vitamin D level of the body. This indicator can regulate the metabolism of calcium and phosphorus in the human body and promote calcium absorption and reabsorption, as well as bone deposition, and has a positive effect on the maintenance of bone health [ 8 ]. IGF-1, a single-chain polypeptide, is mainly produced by the liver, skeletal muscle, and many other tissues in response to growth hormone (GH) stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…25-(OH)D has long been existed in the body and good stability, so it is currently considered to be an important indicator reflecting the vitamin D level of the body. This indicator can regulate the metabolism of calcium and phosphorus in the human body and promote calcium absorption and reabsorption, as well as bone deposition, and has a positive effect on the maintenance of bone health [ 8 ]. IGF-1, a single-chain polypeptide, is mainly produced by the liver, skeletal muscle, and many other tissues in response to growth hormone (GH) stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that deficiency of vitamin D may affect IGF-1 level in children and adolescents exhibiting deficiency of growth hormones like IGF-1 [ 146 ]. VDR polymorphism has also been associated with idiopathic short stature in several studies [ 23 ].…”
Section: Anabolic Steroids and Growth Hormonesmentioning
confidence: 99%
“…In a study conducted on a Chinese population, it was observed that polymorphism in VDR rs2228570a and DBP rs7041 are more responsible for higher susceptibility to hepatitis B virus related HCC [ 22 ]. Recent published trials showing the association between vitamin D and HCC have been documented in Table 3 .VDR polymorphism is also associated with idiopathic short stature in several studies [ 23 ]. Recently, Marek et al has conducted an important study linking growth hormone (IGF-1 axis), Vitamin D and bone mineral density (BMD) in patients afflicted with chronic viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Cxcl12 (C‐X‐C motif chemokine 12), also called SDF1, is the ligand for GPCR, which plays a role in calcium regulation. Vitamin D receptor is essential in the metabolism of minerals, especially calcium (51). Gremlin 1, a biomarker of osteochondroreticular stem cells in the bone marrow, was decreased after PFMG1 treatment, which indicates a loss of stem cell features during osteoblast differentiation (52).…”
Section: Discussionmentioning
confidence: 99%